The concept of person and her axiological relevance: the principles of personalist bioethics. - de Paula, Ignacio Carrasco (Medicina e Morale, 2004)
Bioethics is a reflection that faces with ethical issues concerning human life from a perspective that recognises the being and the dignity of the human person as absolute values. Consequently, it proposes the unconditioned respect of their inviolability and the guardianship of their free expression, as primum principium, first of all at the level of the human rights. In the personalist perspective, Bonum, that is the ultimate value that judges the moral behaviour, is intended as promotion of the being and of the preciousness or dignity of the person like person. The faithful, either moralist or philosopher or bioethicist or someone else, feels at one's ease when his mind goes through ways of the person. In other words, he particularly feels facilitated, like the pilgrim who - after he has gone through inaccessible and unknown ways - finds again family ways. In "home" of the person, faith and reason verify their identity and strength, free from negotiations or unnatural renouncements to own duties and rights; personalist moral philosophy intended as an organic and rigorous synthesis is a desire that have to be realised . For instance, a personalist bioethics would admit larger space to the properly ethical request that is if and why the embryo must be considered as someone else human being, also without explicating the ontological issue. Three fundamental reasons can be produced as the basis of the demonstration of the primacy of the human person. The first is contained in the well-known Aquinas'af firmation: "persona significat id quod est perfectissimum in tota natura, scilicet subsistens in rationali natura". The dignity of the person finds here a deeply ontologic support: who is especially perfect cannot be unrecognised and respected semper et pro semper, in every circumstance of time and place, that is in an absolute way. No created value - neither the overcoming of all illnesses and sufferings - can stand up to the comparison of the value of each person. The second reasons is thanks to I. Kant and it can be interpreted as an application of Aquinas'thesis: the perfettissimum in tota natura being holds out against whatever attempt to lower him to the condition of simple "instrument". As Kant says in the famous paragraph of the Fundamental Principles of the Metaphysic of Morals, the person imposes the categorical imperative to acting in such a way as to always treat the humanity, in you and in the others, as a purpose and never only as a means. Finally; the third reason is caused by a very well known passage, as the previous ones, even if it is not very utilised, perhaps because of its theological content. We refer to the anthropological definition of Gaudium et spes of the Second Vatican Ecumenical Council, according to that the man is "the only creature who God willed for hitself".